If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6t + -6 = 9t + -36 Reorder the terms: -6 + 6t = 9t + -36 Reorder the terms: -6 + 6t = -36 + 9t Solving -6 + 6t = -36 + 9t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-9t' to each side of the equation. -6 + 6t + -9t = -36 + 9t + -9t Combine like terms: 6t + -9t = -3t -6 + -3t = -36 + 9t + -9t Combine like terms: 9t + -9t = 0 -6 + -3t = -36 + 0 -6 + -3t = -36 Add '6' to each side of the equation. -6 + 6 + -3t = -36 + 6 Combine like terms: -6 + 6 = 0 0 + -3t = -36 + 6 -3t = -36 + 6 Combine like terms: -36 + 6 = -30 -3t = -30 Divide each side by '-3'. t = 10 Simplifying t = 10
| k^2+4k-77=0 | | -9.3x+1.8=-52.8-1.5x | | 3.5+2x+5.5=10 | | 4x-10x-40+3=2(x-1) | | 7x+3x=6 | | (7)m-(9)m=(-12) | | x^2+5x+10=0 | | 3(w-2)-6w=-21 | | -2.06d+18=-10.48 | | 3a=144 | | 7m-9m=-12 | | x^2(x+9)+7(x+9)= | | -110=-4c-6c | | 3b+4=15 | | 5x+10=3x+24 | | 11x+(-6x)+11= | | 9r-8=6r+7 | | (x^4+y^2)(x^4-y^2)= | | 3(x+4)-(-4)=2x+8-4 | | 5x^6+5x^5-40x^4+35x^3= | | 2x-x=1.5 | | 4x-10=2x+12 | | x^2=(x-2)*(x+6) | | 3t+9t=60 | | m=n+8 | | 3x+5=5x-9 | | 7u+11.59=32.31 | | 3x+7=6x-11 | | 19x^7-8x^5+16x^4= | | 2x=(x-2)*(x+6) | | -3(1+2v)=90 | | (x-3)(x-1)(2x-5)=6 |